Los caminos de la democracia en el siglo XXI. Los escenarios en América latina - Quiroga, Hugo (SocietàMutamentoPolitica, 2018)
This article analyzes the populist rise, the extreme right-wing progress, the extreme nationalism resurgence, the xenophobia, in a historical context of liberal democratic deficit. As it disappoints, anti-liberalism grows. All these conglomerate, from right to left, it brings together the political and cultural anti-liberalism, which is part of a long tradition of thoughts which exist like a political force and a cultural climate. It is a group of phenomena which encompasses anti-liberalism philosophies. Particularly, the new Latin American political scenarios of the centre-left cycle are studied, headed by Hugo Chavez with the “Socialism of the 21st Century” in Venezuela, and Rafael Correa with the “Citizens’ Revolution” in Ecuador. Nowadays, political analysts and some regional scholars talk about the end of a cycle. Is it the end of the populism cycle in Latin America when populism resurge in Europe and the United States? As a matter of fact, Evo Morales in Bolivia and Daniel Ortega in Nicaragua are the only ones who remain on the Latin-American progressive cycle. In principle, populism is a minority force in electoral terms, since Dilma Rousseff in Brazil, Tabaré Vázquez in Uruguay and Michelle Bachelet in Chile separated from the power. The progressive sectors characterise the present Latin-American process like the backward left and a new forward right. The changing trend started when Mauricio Macri won the Argentine elections at the end of 2015, and it is reasserted with Sebastian Piñera’s triumph in Chile in December 2017. For this tendency to be consolidated, it should be awaited the elections on the three countries which conform 70% Latin-American electorate: Brazil, Mexico and Colombia; which will take place over the course of 2018. These are the explored scenarios to broaden the democratic reality of the 21st century.